2010
DOI: 10.4321/s1130-01082010001200002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the pressures of canal anal and rectal sensitivity in patients with fecal incontinence, chronic constipation and healthy subjects

Abstract: Introduction: There exits a great variability in the manometric findings between patients with anal incontinence (AI) and healthy subjects. The correlation between the pressures of the anal canal and the AI is not exact by the wide rank of normal values.Objectives: Prospective study to evaluate differences in the pressures of the anal canal and in rectal sensitivity in patients with AI, chronic constipation (CC) and healthy subjects.Material and methods: Ninety four patients with AI, 36 patients with CC and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…The precise pathophysiological mechanism why the procedure is effective is unknown, and this may be seen in the medical literature for a variety of anorectal manometry values, both pre-and post-operatively, where various irreproducible effects are described for all series: increased maximum tolerated volume, increased volume at which sensation takes place, and increased sphincter resting pressure (18)(19)(20)(21). In our study, following the procedure we saw that voluntary contraction pressure improved in a statistically significant manner.…”
Section: Discussionmentioning
confidence: 52%
“…The precise pathophysiological mechanism why the procedure is effective is unknown, and this may be seen in the medical literature for a variety of anorectal manometry values, both pre-and post-operatively, where various irreproducible effects are described for all series: increased maximum tolerated volume, increased volume at which sensation takes place, and increased sphincter resting pressure (18)(19)(20)(21). In our study, following the procedure we saw that voluntary contraction pressure improved in a statistically significant manner.…”
Section: Discussionmentioning
confidence: 52%
“…However, the difference in the median resting pressure measured in the erect position from that in the left-lateral position was only 7–8 cm H 2 O in either the CRAI or non-CRAI patients, which would be clinically insignificant to avoid FI especially in the CRAI patients, because the median squeeze pressure was nearly 30 cm H 2 O lower in the erect position than the lateral position. Anal canal length in the lateral position was longer in healthy subjects compared with female patients with FI in previous studies [ 23 , 24 ]. Meanwhile, there was no change in the anal canal length with a change in the posture in the healthy adults [ 9 ].…”
Section: Discussionmentioning
confidence: 69%
“…Besides patients with FI, those with non-prolapsing hemorrhoids also have a thicker anal cushion and, thus, a higher resting pressure [18]. Anal canal length in the lateral position was greater in healthy subjects compared with female patients with FI in previous studies [19,20]. Meanwhile, there was no change in the anal canal length with a change in the posture in the healthy adults [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, multiple factors lead to underestimating fecal problems. 4 Although a few studies have reported an association between the presence of constipation and/or FI and reduced quality of life (QoL), 3,[5][6][7] little is known about the association between the severity of constipation or FI and QoL. However, these studies show ambiguous outcomes and are restricted to patient populations.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
“…However, these studies show ambiguous outcomes and are restricted to patient populations. 6,7 A few studies have documented fecal problems in the general population. Nevertheless, only a limited number of publications are dedicated to constipation, FI, and their coexistence in relation to QoL and its different domains of people struggling with such problems.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%